Analisis Metode 5S Pada Stasiun Kerja Pembuatan Rumah Boneka - Tiara Tiara; Surya Perdana; Atikah Atikah (LPPM, 2020)
On the production floor CV. There are 6 work stations that produce wooden dollhouses. All activities carried out by workers are carried out simply with irregular production floors where workers put the tools and materials used out of place which causes the workspace to be more narrow and work risks arise. To correct this, an analysis of the work environment will be carried out using 5S. The formulation of the problem is done through observations made on the production floor CV. RB. The review is carried out on the current work environment layout and the problems that occur in it. The identification results are used as a basis for compiling the concept of applying 5S in accordance with the characteristics of the production floor CV. RB. Analysis of the impact caused by the existing conditions is the result of observations and interviews with relevant parties. Furthermore, this research will give a proposal to solve the problems in the production of dollhouses using 5S. One of the improvements made is the provision of training on the basic concepts of 5S. By using 5S there will be improvements where workers will become disciplined, reduce waste and work risks.